Disturbed body schema, perceptual body image, and attitudinal body image in patients with borderline personality disorder - Szily, Dorottya; Kelemen, Rebeka; Nagy, Zita S.; Szabó, Dominik; Unoka, Zsolt Szabolcs (Frontiers in Psychiatry, 2023)
Background: Borderline personality disorder(BPD) is a severe mental disorder that affects attitudes toward the body, but we do not know if there is any disturbance at the level of body schema and perceptual body image. Previous questionnaire-based studies found dissatisfaction with one's body in BPD. In addition to attitudinal body image, our study investigates whether body schema and perceptual body image are disturbed in BPD.Method: Our study included 31 patients diagnosed with BPD(25 women) and 30 healthy individuals(19 women) (Mage=29 for both groups). SCID-5-PD interview was used to determine personality disorder. Attitudinal body image was measured using the Body Attitude Test(BAT) factors. Body schema and perceptual body image were measured by two conditions of a body representation task, the Body Portraying Method(BPM).Results: BPD patients reached higher scores in all three BAT factors and were more misled in both conditions of BPM. Based on the results, borderline patients appear to have a more negative attitude toward their body and worse perceptual body image and body schema.The novel finding of our study is that besides the previously found attitudinal dissatisfaction with the body, there are disturbances in the body schema and perceptual body image level in BPD. Our findings on body schema and perceptual body disturbances need further research on their etiological factors and provide new therapeutic targets for the treatment of BPD.